Hubungan Indeks Massa Tubuh Terhadap Kelincahan Pemain Futsal Academy Al-Hadid Surabaya Usia 20 Tahun - Raynor Figo Guritno; Abdul Aziz Hakim (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The dominant characteristics of movement in futsal are fast and agile in changing direction of movement, which is explained as agility. To maximize the physical components of agility, an ideal body composition will certainly be needed, which can be seen through the body mass index. Body mass index is a measuring tool to determine a person's ideal body composition through the calculation of weight and height. This study investigates the relationship between body mass index and agility of futsal players at the AL-Hadid Academy Surabaya aged 20 years in 2024. This study uses a quantitative descriptive approach that focuses on correlation. The data collection method is carried out using 2 instruments, including measuring height and weight to calculate body mass index with the formula and conducting an agility test using the illinois agility test which is only measured once on each instrument. Body mass index is the independent variable in this study, and agility is the dependent variable. using descriptive statistical data analysis methods, linearity tests, and product moment correlation analysis. The results of data analysis show that body mass index has a linear relationship in the linearity test with a significant deviation form linearity value of 0.165> 0.05. Then in the product moment correlation test, a significance value of 0.000 and a correlation coefficient value of 0.709 were obtained, which can be said to be correlated, the direction of the relationship is positive, and indicates a very strong degree of relationship. Based on the statistical results, it can be concluded that body mass index has a very strong relationship to the agility of futsal players.